Pseudo Five-Component Synthesis of 3-(Hetero)arylmethyl-2,5-di(hetero)-aryl-Substituted Thiophenes via Sonogashira–Glaser Cyclization Sequence - Klukas, Fabian; Perkampus, Jörg; Urselmann, Dominik; Müller, Thomas J. J. (Synthesis, 2014)
The Sonogashira–Glaser sequence combined with a microwave-assisted cyclization is a powerful tool to synthesize unsymmetrically substituted conjugated thiophenes. A variety of 3-(hetero)arylmethyl-2,5-di(hetero)aryl-substituted thiophenes could be synthesized in moderate to excellent yields using a single Pd/Cu catalyst system. The presented method is strikingly simple to perform using commercially available starting materials. The obtained trisubstituted oligothiophene derivatives are interesting molecules for materials science.
Keywords: copper; cross-coupling; heterocycles; multicomponent reactions; palladium; thiols